(untitled) (Solukhumbu Multiple Campus Research Journal, 2025)
The reflective study examines the current issues in the supervision of undergraduate research project in English education in a community campus in Nepal. The study applies qualitative auto ethnographic and narrative inquiry methodologies to six years of supervisory experience with fourth-year Bachelor students to examine challenges of critical concern to research directions. The results indicate a general lack of academic preparedness among students, as they have minimal knowledge of how to conduct research, fail to engage with a topic deeply, and cannot use terms such as sampling and data collection. A culture of plagiarism and heavy reliance on internet sources is an indication of institutional failure to focus on academic integrity education. There is also inappropriate student attendance and submissions at the last moment, which further interferes with the continuity of supervision. There are also notable flaws in the methodological skills of students, as they cannot create research questions, select the appropriate tools, and comprehend the ethical issues; thus, the supervisor has the extra burden of instructing these principles. Supervisors are under emotional and professional pressure and tend to be frustrated and burned out, but the institutions are not aware of it. These are worsened by institutional loopholes, including lack of orientation programs, no clear supervision policies, and a poor research culture. The research proposes systemic solutions such as integrating research skills in the curriculum, institutional training of supervisors, and a campus-wide focus on research ethics and research participation as possible solutions to enhance the performance of students and the performance of the supervisors in under-resourced academic institutions.